Analysis of Consumer Satisfaction Level Towards Banana Nuggets (Case Study of Banana Braga Ambon) - Sulaiman, Saldiva; Kakisina, Leunard Onosivorus; Tuhumury, Maisie Trixie Flori (PT FORMOSA CENDEKIA GLOBAL, 2024)
The creation of processed agricultural products such as banana nuggets may open up opportunities for banana agro-industry operators to take advantage of the existing business opportunities. The emergence of similar business offering the same goods and marketing different products can certainly encourage consumers to be more selective their purchasing decisions. Banana nuggets are an innovative form of processed banana snack. This study aims to analyze the level of consumer satisfaction towards the attributes of banana nugget products at Banana Braga Ambon. The population and sample in this study consisted of 100 respondents from Ambon City who happened to buy banana nuggets at Banana Braga Ambon (Accidental Sampling). This study used descriptive analysis method, Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). This study shows that the level of consumer satisfaction towards the attributes of banana nugget products at Banana Braga is 0.87. This means that the results indicate that consumers are very satisfied with the product attributes as the satisfaction level is in the category of 0.81 - 1.00